Laboratory data on the interfacial tension, viscosity, and density of two naphthenic acids in n-hexadecane across varying temperatures and concentrationsPUrE - Mohammad Sarlak; Alan J. McCue; Yukie Tanino (Data in Brief)
This paper presents oil-brine interfacial tensions measured using the pendant drop method at temperatures ranging from T = 25.0 to 60.0°C. Test oils were solutions of stearic acid or cyclohexanepentanoic acid in n-hexadecane at concentrations ranging from 0 to 2200 mg/L; the test brine was 5 wt.% NaCl and 1 wt.% KCl in deionized water for all measurements. Also presented are viscosity and density measurements by rotational viscometry at temperatures ranging from T = 20.0 to 80.0°C.